A Tricky Subject – archaeology in opinion polls on cultural heritage. Recent examples from Poland - Agnieszka Oniszczuk (Internet Archaeology, 2021)
Understanding the public by analysing the wants, interests and expectations regarding their involvement in archaeology is one of the strategic aims of Europae Archaeologiae Consilium (EAC). Cultural heritage has been the topic of several public opinion polls in Poland over the past few years. In 2011 and 2015, the Narodowy Instytut Dziedzictwa (National Institute of Cultural Heritage) carried out two representative surveys. Subsequent polls focusing on more specific issues or groups of respondents were undertaken in 2015, 2017 and 2018. Other data from Poland come from the 2017 Special Eurobarometer survey on cultural heritage. They can be contrasted with archaeology-orientated opinion polls: a Europe-wide survey carried out within the NEARCH project led by Inrap (French National Institute for Preventive Archaeological Research) and several smaller-scale projects, which might be treated as starting points for more representative research.